IMPROVING THE CAPABILITIES OF WRITING NARATION OF JAPANESE LANGUAGE THROUGH THE DRAWING MEDIA IMAGE SERIES (ACTION RESEARCH IN SMK NEGERI 18 JAKARTA) - Nurainih, Nurainih (IJLECR (International Journal of Language Education and Cultural Review), 2018)
This action research aims to improve students’ ability in writing Japanese narrative through the medium of series images. The subjects of this study are students of class XI Accounting at SMK Negeri 18 Jakarta, the year of learning 2016-2017. The research data was collected through observation, prates, collaborator notes, and final tests of each cycle. This action research model uses the research model of Kemmis and Mc Taggart action that is planning, action, observation, and reflection. This study was conducted for two months consisting of eight meetings in two cycles. Four cycles meeting I and four cycle II meetings. Improvements are made in each cycle and follow the post test at the end of the lesson. Research data were analyzed through qualitative and quantitative procedures. The result of the research stated that the students’ ability in writing Japanese language narration in cycle I was only 68.5 and cycle II became 83.2. Based on that, the medium of the series image can improve students’ ability in writing Japanese narrative.